Effects of indoor slippers on plantar pressure and lower limb EMG activity in older women. (September 2016) - Yick, K.L.; Tse, L.T.; Lo, W.T.; Ng, S.P.; Yip, J.
Abstract: Open-toe mule slippers are popular footwear worn at home especially by older women. However, their biomechanical effects are still poorly understood. The objective of this study is to therefore evaluate the physical properties of two typical types of open-toe mule slippers and the changes in plantar pressure and lower limb muscle activity of older women when wearing these slippers. Five walking trials have been carried out by ten healthy women. The results indicate that compared to barefoot, wearing slippers results in significant increases in the contact area of the mid-foot regions which lead to plantar pressure redistribution from metatarsal heads 2–3 and the lateral heel to the midfoot regions. However, there is no significant difference in the selected muscle activity across all conditions. The findings enhance our understanding of slipper features associated with changes in biomechanical measures thereby providing the basis of slipper designs for better foot protection and comfort. Highlights: Walking with slippers can increase foot contact area at foot landing. Wearing slippers can redistribute pressure over the plantar of the foot. The EMG differences between the slippers and barefoot were not significant. Soft slippers with a more compliant footbed result in a higher perception of comfort.